Pengaruh Tingkat Pendidikan Terhadap Kemiskinan di Provinsi Jawa Timur - Mahardhika Harilinawan; Joshua Filmon Wongso Setiawan; Ihza Riswanda Basuki; Joseph Emiliano Junior; Virgi Ainun Iqbal; Fahrur Rosi; Afifahtus Syaleha; Muhammad Ilham Januarta; Arga Christian Sitohang (Student Scientific Creativity Journal, 2024)
This research aims to determine and analyze the influence of education level on poverty in East Java Province. The research method used in this research is descriptive quantitative using secondary data from the Central Statistics Agency in 2023. The data analysis method used is chi square analysis (X²). The research results show that the level of education influences poverty in East Java Province. The lower the level of education, the higher the level of poverty.